Perancangan Brand Guideline Brawijaya Delight (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
Brawijaya Delight is an MSME that operates in the chocolate industry. MSMEs need a brand identity to differentiate similar MSMEs, so that they are known to the wider community. The problem faced is to determine the brand identity and keep it consistent, a brand guideline or brand guidelines are needed, so that it can protect the brand from inconsistencies and misinterpretation. Therefore, to determine the brand identity of Brawijaya Delight, we collaborated with Kawakibi Digital Branding to form a brand guideline. Brand guideline design consists of a logogram, logotype and mockup. The design of this writing uses qualitative research methods based on interviews, observation and literature study. This research method is used to adapt to the wishes of Brawijaya Delight MSME owners. It is hoped that it can attract consumers and increase income. Design results according to requirements such as logos, logo mockups, logo descriptions, typography and color palettes.